Aktualisasi Agama Sikh di Indonesia Melalui Media Online - Wiranto, Erham Budi (Program Pascasarjana UKIM, 2024)
This study aims to understand the efforts of the Sikh religion in Indonesia to actualize itself within the context of online media development. Although Sikh adherents are scattered across various locations, the study focuses on the activities of the Sikh community at the Guru Nanak Social Foundation, the most active Sikh community in utilizing online media, particularly through its YouTube channel, to maintain their identity and culture amidst Indonesia's religious diversity. The research employs a qualitative analysis method on the content produced by this community, including the *